Distinct tyrosine phosphorylation sites in ZAP-70 mediate activation and negative regulation of antigen receptor function. - Kong, G (1996)
Biochemical and genetic evidence has implicated two families of protein tyrosine kinases (PTKs), the Src- and Syk-PTKs, in T- and B-cell antigen receptor signaling. ZAP-70 is a member of the Syk-PTKs that associates with the T-cell antigen receptor and undergoes tyrosine phosphorylation following receptor activation. Three tyrosine residues, Tyr-292, -492, and -493, have been identified as sites of phosphorylation following T-cell antigen receptor engagement. Utilizing ZAP-70- and Syk-deficient lymphocytes (Syk-DT40 cells), we provide biochemical and functional evidence that heterologous trans-phosphorylation of Tyr-493 by a Src-PTK is required for antigen receptor-mediated activation of both the calcium and ras pathways. In contrast, cells expressing mutations at Tyr-292 or -492 demonstrate hyperactive T- and B-cell antigen receptor phenotypes. Thus, phosphorylation of ZAP-70 mediates both activation and inactivation of antigen receptor signaling.